INVENTARISASI JENIS POHON TEMPAT HABITAT BURUNG CENDRAWASIH DI KAMPUNG NANGGOUW DISTRIK SAUSAPOR KABUPATEN TAMBRAUW - Gidion Sisdifu; Yetti S. Serkadifa; Yerrynaldo Lopies; Lanny Wattimena (SOSCIED, 2026)
This study aims to inventory the tree species used as activity sites by the Birds of Paradise in Nanggouw Village, Sausapor District, Tambrauw Regency. The Bird of Paradise is an endemic fauna of Papua that highly relies on forest habitat conditions, particularly specific tree species utilized for foraging, sheltering, perching, and nesting. The research method applied was a field survey through direct observation and interviews with the local community. The collected data were analyzed descriptively to identify the tree species frequently used by the Birds of Paradise. The results show that the Birds of Paradise utilize various tree species for their activities. The most frequently used tree species include the wild nutmeg (Canarium sp.), wild banyan (Ficus sp.), red fruit tree (Pandanus conoideus), and wild Governor's plum (Flacourtia sp.). These trees play a crucial role as food sources, shelters, and nesting sites for the Birds of Paradise. The presence of these tree species significantly influences the survival of the Birds of Paradise in their natural habitat. Based on the research results, it can be concluded that the availability of specific trees is vital for the conservation of the Birds of Paradise. Therefore, forest conservation efforts and the protection of habitat trees need to be carried out sustainably to maintain the Bird of Paradise population and preserve biodiversity in Nanggouw Village, Sausapor District, Tambrauw Regency.